Browsing Different Instagram Profiles and Associations With Psychological Well-Being - Burnell, Kaitlyn; George, Madeleine J.; Underwood, Marion K. (Frontiers in Human Dynamics, 2020)
Social networking sites (SNSs) may be transforming young people's social experiences, and browsing SNSs in particular may harm psychological well-being. However, browsing different types of SNS profiles may differentially relate to psychological well-being. In a large and ethnically diverse sample of emerging adults (N = 405), this experimental study examined changes in state affect and self-perceptions after browsing one of three different types of profiles on Instagram: an acquaintance, an influencer, or one's own profile. Moreover, this study investigated how individual characteristics may moderate relations between browsing and well-being, by exploring feedback seeking behaviors and the fear of missing out. Browsing one's own Instagram profile led to positive changes in psychological well-being, whereas browsing the profile of either an acquaintance or an Instagram influencer led to negative changes in psychological well-being. Many observed effects, especially those found for the acquaintance and influencer conditions, were moderated by participants' dispositional levels of the fear of missing out and feedback seeking, in which effects were primarily observed for those higher in these characteristics. Findings suggest that SNSs may have positive or negative effects on well-being depending on who is online and what those individuals are browsing.